Impact of a community contraceptive counselling intervention on adolescent fertility rates: a quasi-experimental study - Elia Diez; Maria J. Lopez; Gloria Perez; Irene Garcia-Subirats; Laia Nebot; Ramon Carreras; Joan R. Villalbi (BMC, 2020)
Abstract Background From 2000 to 2008, in urban areas in Spain, adolescent fertility and abortion rates underwent unprecedented increases, consecutive to intensive immigration from developing countries. To address unmet needs for contraception information and services, a community-based, gender-sensitive and culturally adapted brief counselling intervention (SIRIAN program) was launched in some deprived neighbourhoods with a high proportion of immigrants in Barcelona. Once a randomized controlled trial demonstrated its effectiveness in increasing the use of contraceptives, we aim to examine its population impact on adolescent fertility rates. Methods Quasi-experimental study with comparison group, using population data from 2005 to 2016. Five neighbourhoods in the lowest tercile of Disposable Household Income were intervened in 2011-13. The comparison group included the three neighbourhoods which were in the same municipal district and in the lowest Disposable Household Income tercile, and displayed the highest adolescent fertility rates. Generalized linear models were fitted to assess absolute adolescent fertility rates and adjusted by immigrant population between pre-intervention (2005-10) and post-intervention periods (2011-16); Difference in Differences and relative pre-post changes analysis were performed. Results In 2005-10 the intervention group adolescent fertility rate was 27.90 (per 1000 women 15-19) and 21.84 in the comparison group. In 2011-16 intervention areas experienced great declines (adolescent fertility rate change: − 12.30 (− 12.45 to − 12.21); p < 0.001), while comparison neighbourhoods remained unchanged (adolescent fertility rate change: 1.91 (− 2.25 to 6.07); p = 0.368). A reduction of − 10.97 points (− 13.91 to − 8.03); p < 0.001) is associated to the intervention. Conclusion Adolescent fertility rate significantly declined in the intervention group but remained stable in the comparison group. This quasi-experimental study provide evidence that, in a country with universal health coverage, a community counselling intervention that increases access to contraception, knowledge and sexual health care in hard-to-reach segments of the population can contribute to substantially reduce adolescent fertility rates. Reducing adolescent fertility rates could become a feasible goal in cities with similar conditions.